Edukasi Interaktif "Jantung Sehat Kita" Peningkatan Pemahaman Fisiologi Jantung pada Remaja Melalui Media Digital - Lilik Pranata; Bangun Dwi Hardika; Vincencius Surani; Ketut Suryani; Veroneka Yosefpa Winda Handayani; Sri Indaryati; Novita Elisabeth Daeli; Masayu Azizah; Nilda Lely (Jurnal Pelayanan Masyarakat, 2025)
The heart is a vital human organ that plays an important role in the circulatory system. Therefore, an understanding of the heart needs to be given from an early age, starting from basic concepts to more complex aspects. Every human being is created by God with a heart that functions to sustain life, so every individual has the right to gain knowledge about heart health. Adolescents, in particular, need to understand the function and workings of the heart early in order to lower the risk of heart disease in the future. This Community Service (PkM) activity aims to improve the understanding of cardiac physiology in adolescents through the use of digital media. The activity method used is health education about cardiac physiology and how to maintain heart health from an early age. The participants of the activity were 50 students of Madrasah Ibtidaiyah and Junior High School of the Ummul Quro Al-Hamidiyah Foundation. The activity began with the delivery of educational materials, then continued with an evaluation of students' understanding. The results of the activity showed an increase in student knowledge, which indicates that education is effective in forming awareness and early prevention of heart disease.